Caracterización química y microbiológica de abonos orgánicos a partir de gallinaza y rastrojos de cosecha para la producción agrícola - Leveau Tuanama, Roberto (2009)
This research paper entitled: "Chemical and biological characterization of organic fertilizers from chicken manure and crop stubble on agricultural production, are: 1) Characterize the microbiological and chemical manure produced and 2) determine the cost benefits of the treatments evaluated. The work was carried out in E.E. "Juan Bernito" – ICT. It´s a design used a randomized complete block (DBCA) with 5 treatments and 3 replications. The treatments studied were: T0 (50kg of weeds + 50kg of Plantain crop stubble + 50Kg of Pineapple + 50Kg of Shell cocoa), T1 (100Kg of chiken manure + 100 kg of Weed), T2 (100Kg of Chiken manure + 100Kg of Banana crop), T3 (100 kg of Chicken manure + 100Kg of Pineapple crop) and T4 (100Kg of Chiken manure + 100Kg of Shell cocoa). From which the following parameters were evaluated: temperature, humidity, chemical and microbiological characteristics. The results indicate the following: The treatment was the best chemical and microbiological characteristics was the T2, which showed the following results: pH (8.29%), nitrogen (1.19%), phosphorus (1.55%), potassium ( 1.74%), calcium (7.11%), magnesium (0.76%), iron (2797.26 ppm) and manganese (664.17 ppm), fungi (19 556 ufc), bacteria (3.8 x 10 ⁷ ufc) and nematodes (102 indv. / 100 g soil). Regarding the cost / benefit, the treatment had the largest gain was the T1 with a cost / benefit ratio of 52.46%, is for each reversed sun was a gain of S /. 0.48 nuevos soles.